A GNN-based model for capturing spatio-temporal changes in locomotion behaviors of aging C. elegans. (March 2023) - Yuan, Ye; Xin, Kuankuan; Liu, Jian; Zhao, Peng; Lu, Man Pok; Yan, Yuner; Hu, Yuchen; Huo, Hong; Li, Zhaoyu; Fang, Tao
Abstract: Investigating the locomotion of aging C. elegans is an important way for understanding the basic mechanisms behind age-related changes in organisms. However, the locomotion of aging C. elegans is often quantified using insufficient physical variables, which makes it challenging to capture essential dynamics. To study changes in the locomotion pattern of aging C. elegans, we developed a novel data-driven model based on graph neural networks, in which the C. elegans body is modeled as a long chain with interactions within and between adjacent segments, and their interactions are described by high-dimensional variables. Using this model, we discovered that each segment of the C. elegans body generally tends to maintain its locomotion, i.e., tries to keep the bending angle unchanged, and expects to change the locomotion of the adjacent segments. The ability to maintain its locomotion strengthens with age. Besides, a subtle distinguish in the changes in the locomotion pattern of C. elegans at various aging stages were observed. Our model is anticipated to provide a data-driven method for quantifying the changes in the locomotion pattern of aging C. elegans and for mining the underlying causes of these changes. Highlights: A GNN-based model for capturing spatio-temporal changes in motion of C. elegans. C. elegans body is modeled as a long chain of several interconnected segments. The segments of C. elegans tend to keep own motion and alter that of neighbors. The ability of each segment to keep its own motion state strengthens with age. C. elegans exhibits slightly variable locomotion patterns at various ages.